An fsQCA approach to identifying pathways for digital-professional integration in engineering education - Ye Zhang; Zhida Feng; Xinrong Chen (Humanities & Social Sciences Communications)
Abstract Amid the accelerating wave of digital transformation, engineering education is confronted with structural challenges such as outdated curricula and a persistent misalignment with evolving industry demands. Conventional engineering programs have historically prioritized professional skills development while overlooking the cultivation of digital competencies, leaving graduates ill-equipped to navigate the complexities of an increasingly digital labor market. This study introduces the concept of Digital-Professional Integration (DPI) and investigates how the integration of digital and professional skills influences the development of vocational competence. Drawing on a case study involving 36 students enrolled in a tourism management program at a higher vocational institution in China, the research implemented a one-month digital skills training intervention. Utilizing Fuzzy Set Qualitative Comparative Analysis (fsQCA), the study identifies multiple causal configurations that lead to enhanced vocational competence. Key findings highlight the centrality of market research abilities and information processing skills, alongside the critical role of self-efficacy as a motivational driver. The study offers empirical validation for the DPI framework and contributes to ongoing discourse on interdisciplinary curriculum design, providing actionable insights for reforming engineering education in response to the digital economy.